PENGGUNAAN MEDIA BIG BOOK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS II DI SDN 01 KOTAPINANG - Salmida Sima Aini Siagian; Mardianto Mardianto; Ramadan Lubis (Kampus Akademik Publiser, 2025)
This study aims to determine how the use of Big Book media to improve the reading skills of grade II students at SDN 01 Kotapinang. This study uses a descriptive qualitative research method. The results of this study use observation data, interviews, tests and field notes. The results of test 1 obtained results using reading media obtained that there were 5 students whose scores were